Recycling polyphenylene sulfide (PPS): A comprehensive review of mechanical, thermal and physical properties for aerospace engineering applications - Mustafa, Nuzaimah; Lee, Jing Yuan; Razali, Nadlene; Hamdan, Hasanudin; Merzeik, Laurent (Penerbit Universiti Kebangsaan Malaysia, 2025)
Polyphenylene Sulfide (PPS) is a high-performance thermoplastic widely utilized in aerospace applications due to its exceptional mechanical, thermal, and chemical resistance properties. However, the increasing demand for PPS based materials has led to significant waste generation, posing sustainability challenges. This review explores the feasibility of PPS recycling for aerospace applications, addressing key knowledge gaps, limitations, and environmental implications. Despite advancements in mechanical and chemical recycling techniques, challenges remain in maintaining the mechanical integrity of recycled PPS, particularly in fiber-reinforced composites. Polymer degradation, chain scission, and contamination affect recycled PPS properties, reducing tensile strength, impact resistance, and crystallinity, which limits its application in load-bearing aerospace components. Furthermore, the lack of standardized testing and certification processes for recycled PPS in aerospace remains a critical gap that hinders widespread adoption. Recycling PPS presents sustainability benefits, particularly in reducing polymer waste, minimizing carbon emissions, and promoting circular economy initiatives. Mechanical recycling offers cost-effective material recovery but results in compromised mechanical performance due to thermal and shear degradation. Chemical recycling, while capable of restoring polymer purity, is hindered by high energy demands and the use of hazardous chemicals. Innovations in reinforcement strategies, such as the integration of glass or carbon fibers, have shown potential in restoring mechanical properties, making recycled PPS suitable for non-structural aerospace applications like aircraft interiors, ventilation systems, and protective enclosures. This review emphasizes the need for further research into optimizing recycling techniques, improving process scalability, and establishing regulatory frameworks to ensure the structural reliability of recycled PPS in aerospace applications.